Basic Trauma Cardiac Life Support Training Management on Senior High School Students - Syahferi Anwar; Arief Rahman Aceh; Balqis Nurmauli Damanik; Hely Hely (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Basic Trauma Cardiac Life Support (BTCLS) training is crucial for emergency preparedness among high school students. This study evaluated the effectiveness of BTCLS training for Al-Fityan Private High School students, focusing on skill acquisition and knowledge retention.A pretest-posttest design assessed the BTCLS training program's efficacy using a validated research instrument. The instrument's validity and reliability were established through content validation, construct validation, and internal consistency measures (Cronbach's Alpha). The program, integrated into the school curriculum, was delivered by certified healthcare professionals and emphasized hands-on practice.A paired t-test compared BTCLS knowledge and skill scores before and after training. Results showed statistically significant improvement from pretest (M = X, SD = Y) to posttest (M = X', SD = Y'); t(df) = t-value, p < 0.05. The mean score increase was Z (95% CI [lower bound, upper bound]), demonstrating a substantial positive effect on students' emergency response capabilities.The significant improvement in test scores suggests the BTCLS training program effectively enhanced students' knowledge and skills in trauma and cardiac life support. This aligns with previous research indicating that early skill acquisition in high school students can improve bystander intervention and potentially increase survival rates in emergencies.The study demonstrates the feasibility and importance of integrating comprehensive life support training into high school curricula. Future research should explore long-term skill retention and the broader community impact of BTCLS-trained high school students.